Annual statistical abstract (Lagos Ascon, 1984)
This annual reports contains some of the activities of the administrative staff college of Nigeria in 1984. It also reveals administrative position and training embarked upon by the institute.
asm; 05/03/19
Loans
Keywords: Administrative college of Nigeria; Nigeria